KWAME NKRUMAH AND THE PAN-AFRICAN IDEAL debates and contestations. - MAKGETLANENG, SEHLARE (INST FOR PRESERVATION AND, 2021)
Kwame Nkrumah and the Pan-African Ideal draws on experiences in various decades on the ebbs and flows of African continental integration as a common African continental agenda. It attempts to contribute towards the grasp of critical theoretical position on international political economy and its application on the African socio-political, economic and ideological condition. This work critically engages with the works of Nkrumah, a leading African scholar on the African continental political unity in the political, economic and ideological fields of the struggle to achieve the continental socio-political, economic and ideological transformation in the strategic interests of Africa in its continental and international relations. As a means of demonstrating invaluable knowledge produced by Nkrumah for a critical engagement in the efforts to achieve African continental integration and transformation, this work provides a critical analysis of his position on the African continental integration and how the decisive majority of heads of state and government from the Organisation of African Unity to the African Union (AU) have waged the struggle against it.